Achieving regional sustainable development: a bibliometric analysis on firm migration. (6th June 2023) - Fan, Liu; Wang, Yichen; Zhao, Zhongchao; Liu, Xinmin; Wang, Lei
Firm migration has significant influence on the local industrial transformation and regional economic development. Meanwhile, the impetus of globalisation has intensified firm migration, which, in turn contributes to business formation and diversification. Therefore, this study conducts a comprehensive literature review pertaining to this area through bibliometric analysis and further discusses the bidirectional relationship between firm migration and regional economic development. Top-tier journals, important institutes and hot topics are taken into analysis by CiteSpaceV to quantitatively and visually evaluate scientific documents from Web of Science (WoS) published between 2000 and 2017. The results identified that major studies of firm migration mainly concentrate on the USA, the UK and China. Using co-citation analysis, hot topics are found mainly focusing on theoretical research, driving factors on firm migration and related economic phenomena caused by firm migration. Considering the trends, 'Value Chain', 'Environment' and 'Multinational' are possible prevalent research topics in the coming years. For revealing the relationship between firm migration and regional economic development, burst detection and research trend analysis are conducted considering typical economic issues. The results show that firm migration is a significant management decision, which has the capability to provide managerial solutions for governments as a strategy to confront certain economic issues, which in turn, will promote the sustainable development of regional economy.